Proposed Sales Strategy in Herbal Medicine Products Using the Association Rule Method for Trimitra Herbal Pharmacy - Sugandi, Gagan; Adriansyah Anwar, Tezza; Purno Wahyu Wibowo, Ari (International Journal of Engineering and Technology, 2018)
Pharmacies are a place for selling drugs based on a prescription from a doctor. Pharmacies themselves have a close relationship with pharmaceutical companies and of course the Ministry of Health as a regulator related to the sale and marketing of drugs to the public. The main task of a pharmacy is to distribute drugs and provide a report data recap. At present, the problems faced in drug distribution are the uneven demand for drug distribution. Sometimes, the drug runs out or excess stock will be problematic with the accumulation of the amount of goods in the warehouse and can become expired and can be dangerous if distributed to the public. To overcome this problem, a computerized system was created. The system functions to recap the amount of goods and provides a recommendation on what items are most purchased by customers or patients. The method used is by using the Association rule Algorithm. The algorithm can display the number of relationships or relationships of the most sold products from 20% to 80% by calculating the value of support and confident.Â Â